Methods for Human History - Manning, Patrick. author. aut Link
IX, 199 p. 4 illus., 1 illus. in color.
Keywords: This book presents a concise yet comprehensive survey of methods used in the expanding studies of human evolution, paying particular attention to new work on social evolution. The first part of the book presents principal methods for the study of biological, cultural, and social evolution, plus migration, group behavior, institutions, politics, and environment. The second part provides a chronological and analytical account of the development of these methods from 1850 to the present, showing how multidisciplinary rose to link physical, biological, ecological, and social sciences. The work is especially relevant for readers in history and social sciences but will be of interest to readers in biological and ecological fields who are interested in exploring a wide range of evolutionary studies. .